Postoperative Pain Treatment with Continuous Local Anesthetic Wound Infusion in Patients with Head and Neck Cancer: A Nonrandomized Clinical Trial - Gostian, Magdalena; Loeser, Johannes; Albert, Carola; Wolber, Philipp; Schwarz, David; Grosheva, Maria; Veith, Stephanie; Goerg, Christoph; Balk, Matthias; Gostian, Antoniu Oreste (JAMA Otolaryngology - Head and Neck Surgery, 2021)
Importance: Up to 80% of patients with head and neck cancer undergoing ablative surgery and neck dissection develop postoperative pain with detrimental effects on quality of life that also contributes to neuropathic and chronic postoperative pain. Objective: To investigate the association of continuous local anesthetic wound infusion with pain management after head and neck surgery. Design, Setting, and Participants: This prospective, longitudinal, nonrandomized clinical study carried out in a single tertiary referral center (December 1, 2015, to July 1, 2017) included 2 groups of 30 patients. Patients were consecutively enrolled and presented for ablative head and neck surgery including selective neck dissection and studied from the preoperative through the fourth postoperative day. Interventions: The control group was treated according to a standardized escalating oral treatment protocol (ibuprofen, metamizole, opioids). The intervention group was treated with an intraoperatively applied pain catheter (InfiltraLong plus FuserPump, Pajunk, ropivacaine, 0.2%, 3 mL/h) that was removed 72 hours after operating. Main Outcomes and Measures: Average and maximum pain intensities on a numeric rating scale; quality of life using the acute version of the validated 36-Item Short Form Survey; and neuropathic pain using the validated 12-Item painDETECT questionnaire. Consumption of opioid and nonopioid analgesics and evaluation of catheter-associated complications. Results: During postoperative days 1 through 4, patients of the intervention group (mean [SD] age, 63.2 [13.3 years; 9 [30%] women) experienced lower mean (SD) (1.6 [1.4] vs 2.7 [1.8]; η2p= 0.09 [0.01-0.21]) and maximum (2.4 [2.2] vs 4.2 [2.0]; η2p= 0.11 [0.01-0.24]) pain intensities compared with the control group (mean [SD] age, 62.5 [13.6] years; 5 [17%] women). The intervention group also reported less neuropathic pain (mean [SD], 5.4 [3.4] vs 7.6 [5.1]; η2p= 0.09 [0.004 - 0.22]) and higher quality of life regarding vitality (56.2 [21.5] vs 43.8 [20.9], r = 0.29; 95% CI, 0.01-0.52) and pain (66.8 [27.3] vs 49.5 [27.7], r = 0.31; 95% CI, 0.04-0.54). Patients from the intervention group requested nonopioid analgesics considerably less often (n = 17 [57%] vs n = 29 [97%]; φ = 0.47; 95% CI, 0.30-0.67) associated with a noticeably lower need to escalate pain treatment (n = 3 [10%] vs n = 9 [30%]; mean [SD] ibuprofen dose: 500 [173] mg vs 1133 [650] mg; r = 0.64; 95% CI, 0.02-0.91). No catheter-associated complications were observed. Conclusions and Relevance: Continuous anesthetic wound infusion is associated with reduced postoperative pain and decreased demand for analgesics. It therefore expands the treatment options for postoperative pain in head and neck cancer. Trial Registration: German Clinical Trials Register: DRKS00009378.
CRIS-Team Scopus Importer:2021-04-19